The Influence of Background Music Teaching on the Accuracy and Fluency of College Students' English Writing in China - Song Yanbei (International Journal of Education and Humanities, 2026)
The study examines the influence of background music on the accuracy and fluency of English writing among college students. It shows that) Background music during teaching can help improve students' lexical accuracy in English writing. To be specific, background music teaching can reduce lexical errors greatly and restrain syntactic errors efficiently, but does not show any advantages in decreasing the students' morphological errors and punctuation errors.2). Compared with traditional teaching, background music teaching can not promote the fluency of English writing of the students.3). Although background music teaching can release students' anxiety, it may not help the students to obtain more comprehensible input. Therefore, teachers should increase opportunities for students to practice English writing and enrich the variety of tasks, enabling them to write relevant compositions. At the same time, teachers should help develop students correct English writing skills and habits; students should accumulate good sentence patterns, recite more excellent compositions and idiomatic expressions to implement them in English writing practice;  students should also increase the practicing frequency and conquer dilemma before English writing to eliminate negative impact in mind, so as to extract relevant information fluently to improve English writing quality